Womanist Midrash / Volume 2 A reintroduction to the women of Joshua, Judges, Samuel, and Kings / Wilda C. Gafney - Gafney, Wilda (Womanist Midrash, 2024)
Continues Gafney's unique and imaginative work of in-depth translation-based explorations of the well- and lesser-known women and girls of the Hebrew Scriptures. This volume focuses on the women in the books of Joshua, Judges, Samuel, and Kings-- Provided by publisher